Uji Aktivitas Anti Bakteri Ekstrak Etanol Dan Fraksi n-Heksana, Etil Asetat, Air Dari Kulit Buah Kakao (Theobroma cacao L.) Terhadap Bakteri Staphylococcus epidermidis ATCC 12228 Dengan Metode Difusi Dan Dilusi - Regita Fortunata; Tatiana Siska Wardani; Desy Ayu Irma Permatasari (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Cacao fruit peel (Theobroma cacao L.) is a plant that can be used as an antibacterial. Cocoa pod shell contains chemical alkaloids, flavonoids, tannins, saponins, triterpenoids. The purpose of this study was to determine the antibacterial activity of the ethanol extract, n-hexane fraction, ethyl acetate fraction, and water fraction from cocoa pod shells to determine the Minimum Inhibitory Concentration (MIC and Minimum Killing Concentration) of the most active fraction of cocoa pod shell on the growth of staphylococcus bacteria. epidermidis ATCC 12228. Cocoa pod powder was macerated using 96% ethanol, then fractionated using n-hexane, ethyl acetate, and water and tested for antibacterial activity using the diffusion and dilution method.Diffusion and dilution methods used the same concentration of 50% preliminary test 25%; 12.5%; 6.25%; 3.125%; 1.565% against Staphylococcus epidermidis ATCC 12228. The results of the antibacterial activity test using the diffusion method showed that the n-hexane fraction, ethyl acetate fraction, and water fraction from cocoa pod shell Each concentration of 50% inhibited the growth of bacteria in the presence of inhibition.The ethanol extract of cocoa pod shells had the greatest inhibition, namely 13.9 mm. The average diameter of the inhibition zone at a concentration of 25%; 12.5%; 6.25%; 3.125%; 1.565% respectively is 13.43 mm; 6.2mm; 4.23mm; 4.06mm; 3.46mm. The results of the dilution method test showed the MIC and KBM values of the ethanol extract, namely 12.5%, based on the results of the study it can be concluded that the ethanol extract has the most active antibacterial content.